Comparison of Stress-induced Martensitic Transformation Under Tension and Compression in Fe-28Mn-6Si-Cr Shape Memory Alloy - Cao Bo; Iwamoto Takeshi (EPJ Web of Conferences, 2018)
In the case of the NiTi alloy, some research works reported that the stress-strain curve differs significantly between tension and compression. It is considered that the difference in stress-induced martensitic transformation behavior may be observed under different loading modes in Fe-based shape memory alloy (Fe-SMA), which is less expensive compared with the widely-used NiTi alloy. In this study, both tensile and compressive tests of Fe-28Mn-6Si-5Cr shape memory alloy, which is one of Fe-SMA, are conducted under quasi-static and impact deformation at various strain rates. During deformation, it is attempted to evaluate the stress-induced martensitic transformation by measuring the volume resistivity as well as temperature for increasing a reliability of the alloy. Furthermore, from the results of volume resistivity at each strain rate, the strain rate sensitivity of stress-induced martensite under tensile and compressive tests is investigated. Additionally, the difference in stress-induced martensitic transformation under tension and compression is studied.